A taxonomic revision of the tristrigella species group of the genus Nemophora Hoffmannsegg (Lepidoptera, Adelidae) from the Philippines, Malaysia, Brunei and Indonesia - Kozlov, Mikhail V. (Zootaxa, 2025)
This study defines and revises the monophyletic tristrigella species group of the genus Nemophora Hoffmannsegg, 1798, characterized by six presumably apomorphic traits, including (but not limited to) a glossy golden vertex and glossy golden basal part of forewing sharply contrasting with the coppery bronze apical part, which features a distinctive pattern of several yellow spots surrounded by dark brown scales. The group comprises four species: N. pendleburyi Kozlov, sp. nov., from Malaysia; N. vitalii Kozlov, sp. nov., from Indonesia, Malaysia and Brunei; N. chalcotechna (Meyrick, 1937) from the Philippines; and N. tristrigella (Walker, 1866) from Indonesia and the Philippines. These species are described and illustrated herein, with identification keys based on external morphology and male genitalia provided. Particular attention is paid to similarities and dissimilarities between N. chalcotechna and N. tristrigella.